Impacts of polyamines on the morpho-physiological characters and proline content of the two different barley cultivars (Bangladesh Journal of Botany, 2023)
Impacts of the exogenously applied polyamines (PAs) on some physiological features and proline content in drought-resistant  barley cultivars (Hordeum vulgare cv. Bülbül-89) and drought-susceptible (Hordeum vulgare cv. Burakbey) were comparatively examined under PEG-6000-simulated drought stress conditions. It was found that drought stress application had adverse impact on all physiological parameters at least 40% compared to that of the control group. It also dramatically increase the proline content of the cultivars. However, exogenously applied PAs (especially Spm on both barley cultivars) under drought stress conditions showed positive effect on all physiological parameters studied. The proline content increased in the presence of all PAs (especially Spd) in drought-susceptible Burakbey cultivar. If in Bülbül-89, polyamine that increases the proline content was Spd only. Among polyamines Cad was found as the polyamine that provided generally the least successful on all parameters.Bangladesh J. Bot. 52(3): 805-812, 2023 (September)